2016
DOI: 10.3892/ijo.2016.3350
|View full text |Cite
|
Sign up to set email alerts
|

Surface vacuolar ATPase in ameloblastoma contributes to tumor invasion of the jaw bone

Abstract: Ameloblastoma is the most common benign odontogenic tumor in Japan. It is believed that it expands in the jaw bone through peritumoral activation of osteoclasts by receptor activator of nuclear factor kappa-B ligand (RANKL) released from the ameloblastoma, as in bone metastases of cancer cells. However, the clinical features of ameloblastoma, including its growth rate and patterns of invasion, are quite different from those of bone metastasis of cancer cells, suggesting that different underlying mechanisms are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 47 publications
0
11
0
Order By: Relevance
“…Previous studies demonstrated that RANKL-positive cells were more commonly distributed throughout the stroma than in tumor cells in AM (40,47,48). The results of the present study indicated that RANKL mRNA was positively expressed in AM tissues rather than in AM cells, confirming that stromal cells are the major source of RANKL in AM.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Previous studies demonstrated that RANKL-positive cells were more commonly distributed throughout the stroma than in tumor cells in AM (40,47,48). The results of the present study indicated that RANKL mRNA was positively expressed in AM tissues rather than in AM cells, confirming that stromal cells are the major source of RANKL in AM.…”
Section: Discussionmentioning
confidence: 91%
“…However, the results of the present study demonstrated only a slight increase in osteoclast formation of osteoclast precursors in response to AM cells and no evidence of RANKL expression in AM cells. Yoshimoto et al (40) also failed to observe detectable expression of RANKL in AM cells. Interestingly, clear expression of IL-8 was observed in AM cells and neutralization of IL-8 prevented osteoclastogenesis induced by the CM of AM cells (data not shown), suggesting that tumor-derived IL-8 is a key factor that directly induces osteoclast differentiation in AM and that the soluble RANKL in the 1X CM of AM cells is too low to induce osteoclastogenesis.…”
Section: Discussionmentioning
confidence: 96%
“…Besides RANKL, the progression also involved matrix metalloproteinases (MMPs). MMP-1, MMP-2, and MMP-9 were released by ameloblastoma (Yoshimoto, et al, 2016).…”
Section: Introductionmentioning
confidence: 95%
“…It is associated with the surrounding bone resorption, which is a series of complex molecular biochemical reactions that includes osteoprotegerin (OPG), receptor activator of NF‐κB (RANK), and receptor activator of nuclear factor kappa‐B ligand (RANKL) mediated by osteoblasts and osteoclasts . RANKL and RANK also play an important role in jaw resorption during the development of the ameloblastomas . Previous studies in the literature showed that biphosphate drugs have a regulatory effect on the OPG/RANKL/RANK system and can significantly inhibit osteoclasts .…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5] RANKL and RANK also play an important role in jaw resorption during the development of the ameloblastomas. [1][2][3][4][5][6][7] Previous studies in the literature showed that biphosphate drugs have a regulatory effect on the OPG/RANKL/RANK system and can significantly inhibit osteoclasts. 8 99 Tc-MDP (Technetium 99 conjugated with methylene diphosphonate), as bisphosphonate drugs, possesses anti-osteoclastogenic activity against receptor activator of nuclear factor-κB ligand (RANKL)-induced osteoclast formation.…”
mentioning
confidence: 99%